EFFECTIVENESS OF WHEY PROTEIN AND SOYMILK ON MUSCLE MASS AND HEMATOCRIT LEVELS OF VOLLEYBALL ATHLETES - Ulvie, Yuliana Noor Setiawati; Nabila, Aphrodhit Justicia; Rosidi, Ali; Labtrobdiba, Zahra (Journal of Sport Science and Fitness, 2024)
Volleyball is one of the team sports that requires robust muscle mass for exceptional performance and endurance. Protein intake contributes to the formation of muscle mass and red blood cells that are tightly linked to hematocrit levels. The objective of this study was to determine the effectiveness of whey protein and soymilk on muscle mass and hematocrit levels in volleyball athletes. The study was a true experiment with a randomized pre-test and post-test design, involving 20 adolescent, male volleyball athletes divided into 2 groups: whey protein and the soymilk group selected by purposive sampling. The research variables were muscle mass and hematocrit levels. Statistical analysis used independent t-test and paired t-test. The results showed increased muscle mass in the whey protein group (3.50 ± 15.04), but the opposite was found in the soymilk (-1.82 ± 6.46), resulting in significant difference in muscle mass changes between groups (p=0.020). Both groups exhibited reduced hematocrit levels (whey protein group = -3.50±7.69; soymilk group= -1.20±6.30), with a significantly higher decrease shown in the whey protein group (p=0.019).